1998
DOI: 10.1007/s001470050145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surgical technique on long-term outcome of pancreas transplantation

Abstract: To date there is no general consensus as to the best surgical technique for pancreas transplantation. Patients with a pancreas transplant functioning for 3 years or more were retrospectively investigated to compare three surgical techniques: segmental graft with duct obstruction (DO), whole graft with bladder drainage (BD), and whole graft with enteric drainage (ED). Several parameters were studied: patient and graft survival, rejection, long-term surgical and medical complications, and endocrine function. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Two recent long‐term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time 197,207 . Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,208–216 and did not improve immunologic outcome of either SPK 187,190‐192,196‐198,205,206,208,214,217,218 or solitary pancreas transplantations 70,171,219 …”
Section: Discussionmentioning
confidence: 99%
“…Two recent long‐term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time 197,207 . Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,208–216 and did not improve immunologic outcome of either SPK 187,190‐192,196‐198,205,206,208,214,217,218 or solitary pancreas transplantations 70,171,219 …”
Section: Discussionmentioning
confidence: 99%